DensityX: A program for calculating the densities of magmatic liquids up to 1,627 °C and 30 kbar - Iacovino, Kayla; Till, Christy B (Volcanica, 2019)
Here we present a standalone program, DensityX, to calculate the densities of hydrous silicate melts (1000s of samples in a single model run) given pressures, temperatures, and major oxide compositions in wt.% in the 10-component system SiO2-TiO2-Al2O3-Fe2O3-FeO-MgO-CaO-Na2O-K2O-H2O. We use DensityX to analyze over 3,000 melt inclusions over a wide compositional range to visualize the distribution of natural silicate liquid densities in the Earth’s crust. The program is open-source, written in Python, and can be accessed and run via an online interface through a web browser at https://densityx.herokuapp.com or by downloading and running the code from a github repository. A companion Excel spreadsheet can also be used to run density calculations identical to those in the Python script but only for one sample at a time. In another example application, we demonstrate how DensityX can be used to constrain density-driven convective cycling in the phonolitic lava lake of Erebus volcano, Antarctica.